Real-Time fMRI Neurofeedback with War Veterans with Chronic PTSD: A Feasibility Study - Gerin, Mattia I.; Fichtenholtz, Harlan; Roy, Alicia; Walsh, Christopher J.; Krystal, John H.; Southwick, Steven; Hampson, Michelle (Frontiers in Psychiatry, 2016)
Many patients with post-traumatic stress disorder (PTSD), especially war veterans, do not respond to available treatments. Here we describe a novel neurofeedback (NF) intervention using real-time functional magnetic resonance imaging (rt-fMRI) for treating and studying PTSD. The intervention involves training participants to control amygdala activity after exposure to personalized trauma scripts. Three combat veterans with chronic PTSD participated in this feasibility study. All three participants tolerated well the NF training. Moreover, two participants, despite the chronicity of their symptoms, showed clinically meaningful improvements, while one participant showed a smaller symptom reduction. Examination of changes in resting state functional connectivity patterns revealed a normalization of brain connectivity consistent with clinical improvement. These preliminary results support feasibility of this novel intervention for PTSD and indicate that larger, well controlled studies of efficacy are warranted